2019
DOI: 10.1503/jpn.180053
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural mechanisms of threat generalization moderate the link between childhood maltreatment and psychopathology in emerging adulthood

Abstract: Stichting the Weijerhorst and by a fellowship of the Dutch Brain Foundation to M. Wichers (Hersenstichting Nederland: 2012 1-03).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 55 publications
5
30
0
1
Order By: Relevance
“…Trauma exposure during these sensitive periods seems to aggravate fear generalization in later life in military veterans with PTSD (Morey et al, ). In line with this, overgeneralization in the expectancy of threat was associated with higher levels of psychopathology in young adults, but only in those with a history of childhood maltreatment (Lange et al, ). In a recent article, we reported on impairments in generalization processes in a preliminary sample of female patients with PTSD related to childhood maltreatment (Thome et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…Trauma exposure during these sensitive periods seems to aggravate fear generalization in later life in military veterans with PTSD (Morey et al, ). In line with this, overgeneralization in the expectancy of threat was associated with higher levels of psychopathology in young adults, but only in those with a history of childhood maltreatment (Lange et al, ). In a recent article, we reported on impairments in generalization processes in a preliminary sample of female patients with PTSD related to childhood maltreatment (Thome et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…Hermann, Bankó, Gál, and Vidnyánszky (2015) revealed that strength of resting-state functional connectivity between FFA and lateral occipital cortex (LOC) predicted the ability to discriminate the identity of noisy face images. Threat generalization is one of the consequences of experiencing extreme (Lange et al, 2019;Morey et al, 2015) and altered activity of the LOC seems to be a part of the neural basis of this process (Lange et al, 2017). Negative association between cumulative stress index and connectivity between the FFA and sLOC probably reflect problems with emotional face discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting clusters were characterized by comparing the individually averaged generalization gradients between subgroups. To this end, we calculated three different indices for each subject: The mean score of the responses to all six conditioned and generalization stimuli (mean responses); the difference between CS+ and CS− responses (CS-differentiation); and the linear deviation score (LDS) 13,46 as an index of linearity of the generalization gradient, calculated as the difference of the mean response to the conditioned stimuli minus the mean response to the generalization stimuli [(CS+ + CS−)/2 – (GS1 + GS2 + GS3 + GS4)/4].…”
Section: Methodsmentioning
confidence: 99%